Cathérine Le Grand dans les écrits de Charles-Joseph de Ligne - Pychowska, Joanna (Studia Romanica Posnaniensia, 2012)
Charles-Joseph de Ligne (1735-1814), a Wallon and European Prince, subject of the Austro-Hungary Empire, a heartbreaker of the French Europe, is considered the most famous representative of literary cosmopolitanism. War, love and writing were inseparable in his life. He took part in numerous military campaigns, serving both Austria and Russia, as a Russian colonel, a commander of the order of Maria Theresa, and an Austrian field marshal. He authored various texts related to war; he admired heroism of Charles II, Conde, the tactics of Frederick II, the strategies of Napoleon, Catherine II. The latter was immortalized in de Ligne’s various texts representing different literary genres. The Prince was clearly fascinated by the Empress, and he depicted her in a positive light as an educated person, both agreable and determined. Can we, however, talk about the documentary character of his work ? Instead, the Prince seems to be a documentalist-interpreter.